The influence of the components of yoga destination development toward tourist satisfaction and revisit intention/ Phattarawadee Rungsimanop and Ann Suwaree Ashton - Rungsimanop, Phattarawadee; Ashton, Ann Suwaree (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This study aims to investigate the relationship between components of yoga destination development, yoga tourist satisfaction and revisit intention, a case study Hua-Hin, Thailand. A quantitative approach was employed using a purposive sampling by collecting data through online survey questionnaire from yoga tourists. A total of 400 samples were received, and the sample were from many countries around the world. A multiple regression with stepwise method was used to analysis data. The findings revealed that and there are two main yoga destination components to consider when developing a yoga tourism destination: firstly, core resources, and secondly, supporting resources to respond to satisfaction and revisit intention. The theoretical contribution, especially the yoga destination development model which stakeholders including yoga studio owners, yoga instructors, government sectors, accommodation owners, and restaurant owners will be the driving force behind the development of yoga destination, prioritizing core and supporting resources and the practical contribution, the authority should take the initiative to plan an effective collaboration that utilizes each stakeholder's competence and can be adopted in order to develop yoga destination and to attract international and domestic tourists to participate in the unique tourism which become popular activity under wellness context.